Preparation of an anti-dexamethasone monoclonal antibody and its use in development of a colloidal gold immunoassay. Issue 6 (2nd November 2017) - Wang, Zhongxing; Zheng, Qiankun; Guo, Lingling; Suryoprabowo, Steven; Liu, Liqiang; Kuang, Hua
ABSTRACT: A lateral flow colloidal gold (CG) immunoassay strip has been developed for detection of dexamethasone (DEX) residues in milk samples. For this purpose, an anti-DEX monoclonal antibody (McAb), based on a DEX succinic anhydride derivative hapten, was prepared and characterized. The McAb showed a high specificity to DEX, the half inhibitory concentration of the antibody was 0.095 ng/mL, its limit of detection (LOD) was 0.017 ng/mL, and its linear range of detection was 0.034–0.265 ng/mL. The developed CG immunoassay had a visual cut-off value of 0.3 ng/mL in phosphate buffered saline (PBS) and 0.5 ng/mL in milk samples. Each test requires 10 min. Analysis of DEX in milk indicated that the results of strip assay had a strong agreement with indirect competitive enzyme-linked immunosorbent assay. Therefore, the CG immunoassay is a sensitive screening method for semi-quantitative and qualitative detection of DEX residues in milk samples.